Acquisition, Application and Utilization of Knowledge in Higher Education Commission (H.E.C) Recognised Universities in Pakistan - Rasheed, Fatima; Guo, Lingling (Asian Journal of Contemporary Education, 2020)
The purpose of this study is to investigate the effect of knowledge acquisition, application and its utilisation influences to enhance the institutional learning in Pakistan. As numerous Pakistani managers hesitant for the acquisition of technology-based knowledge management, its application and after that its utilization in their organizations (Saeed, Tayyab, Anis-Ul-Haque, Ahmad, & Chaudhry, 2010). In this quantitative study 418, close-ended structured questionnaires were distributed and 245 questionnaires were finalized for reliable primary data. The results of the current study showed that knowledge acquisition and utilization have a positive significant impact on institutional learning while knowledge application has a non-significant impact on institutional learning. In the light of results, it is being deduced that their need to devise strategies and methods so that, acquired knowledge could be applied in the institutions and could be utilised by the students and faculty members. In this way, new doors of knowledge would be open for institutional learning.